Increasing mothers' knowledge, and attitudes, and children's oral hygiene index simplified (OHI-S): an experimental study on the “EKARINI” educational method - Eka Rini, Willia Novita; Rusdi, Muhammad; Siburian, Jodion; Kalsum, Ummi; Susilawati, Sri (Padjadjaran Journal of Dentistry, 2024)
ABSTRACTIntroduction: The high incidence of dental caries in children is partly due to the lack of parental participation in estabilishing children's tooth-brushing habits. This research aims to see an increase in the variables tested in the EKARINI, an educational model on mothers’ knowledge, attitudes, and children's OHIS. Methods: This study employs an experimental design, collecting pretest and posttest data from mothers and their children following the intervention.  The intervention provided in this study involved the EKARINI educational model, which included a pre-test and post-test in the form of a questionnaire consisting of several questions about maternal knowledge and attitudes toward dental health, and the control group received standard education using media such as leaflets, videos, and phantom models. The sample consisted of two groups: an intervention group with 20 respondents and a control group with 20 respondents. Data analysis was conducted using either the independent t-test or the Mann-Whitney test. Results: The findings revealed a significant difference between the posttest scores of the intervention group and the control group The p-values indicate significant differences for each variable: knowledge (p = 0.006), attitude (p = 0.016), and OHIS (p = 0.010), showing that the EKARINI educational model effectively improved maternal knowledge, attitudes, and children's oral hygiene compared to the control group. Based on the average value, the group that received the educational model had a higher average value than the control group. Conclusion: The EKARINI educational model is in increasing mothers’ knowledge, attitudes, and better OHIS values.